HOAX DAN BANALITAS KEJAHATAN (Studi Pustaka tentang fenomena hoax dan keterkaitannya dengan Banalitas Kejahatan) - Astrini, Atik (Transformasi, 2017)
In internet, there is no deceits which inflicts polemics, conflicts and discords amid public morethan hoax. Hoax becomes our seorius problem. Hoax effectively provokes and escalates socialand politic tension by tampering sectarian, racial and ideological sentiments. Hoax scrapespeople’s critical thinking as well. This study aimed to describe and analize how hoax misleadspublic perception, disrupts common moral values, and brings people toward a certain situationcalled banality of evil.Key words : hoax, critical thought, banality of evil